E/Z isomerization, solvatachromism and aggregation-induced emission enhancement of donor–acceptor type oligo(p-phenylene vinylene)s. (1st December 2016) - Feng, Cunfang; Li, Jinyu; Han, Xiao; He, Xin; Liu, Liqun; Li, Xiaoxiao; Sun, Xiaoyi; Lu, Ping; Ma, Yuguang
Abstract : A donor–acceptor molecule, PICNDSB, with cyclopenta[ b ]indole as the donor and (1, 4-phenylene)bis(3-phenylacrylonitrile) as the acceptor, is designed and synthesized.PICNDSB shows typical aggregation-induced emission characteristics. The photoluminescence quantum yield ofPICNDSB in dilute THF was only 0.7% and reaches 51.4% in the solid state. Compared with its analogueCzCNDSB, PICNDSB possesses stronger intramolecular charge transfer properties, as revealed from CV measurements, theoretical calculations, and their fluorescence behaviors. Correspondingly, the relatively more efficient electron-donating terminal group of cyclopenta[ b ]indole endows the molecule with a much higher two-photon absorption cross section of 1286 GM compared toCzCNDSB (357 GM).